Double Layer at the Pt(111)–Aqueous Electrolyte Interface: Potential of Zero Charge and Anomalous Gouy–Chapman Screening - Ojha, Kasinath (Angew Chem Int Ed Engl, 2019)
We report, for the first time, the observation of a Gouy–Chapman capacitance minimum at the potential of zero charge of the Pt(111)‐aqueous perchlorate electrolyte interface. The potential of zero charge of 0.3 V vs. NHE agrees very well with earlier values obtained by different methods. The observation of the potential of zero charge of this interface requires a specific pH (pH 4) and anomalously low electrolyte concentrations (<10(−3)  m). By comparison to gold and mercury double‐layer data, we conclude that the diffuse double layer structure at the Pt(111)‐electrolyte interface deviates significantly from the Gouy–Chapman theory in the sense that the electrostatic screening is much better than predicted by purely electrostatic mean‐field Poisson–Boltzmann theory.